Movie, money, marketing: Branding ‘3 Peas in a Pod’ - SMIT, Willem (Institutional Knowledge at Singapore Management University, 2015)
Michelle Chong is a successful actress but a novice producer in Singapore. After her directorial debut success, she decides to produce a local movie set to premier in November 2013 based on a script she had written ten years ago. Chong is still getting used to the business aspect of movie making, but is faced with the added challenge of having to market the movie strategically in Singapore, which had a demographic accustomed to blockbuster Hollywood movies. Among her tactics to keep her movie production costs low were: employing product placement tactics, partnering with a large distribution chain in marketing, and engaging in many co-promotional events such as road shows and interviews with the media. Shortly before the movie release, Chong suffered a setback when the media authorities restricted viewership of her movie to viewers older than 16 years old – this would exclude much of her target audience. Would she be able to convince enough locals to watch her movie? Will possible mistakes in marketing, due to her lack of experience, affect the success of the movie? The case can be used in undergraduate and post-graduate programs to teach concepts related to marketing. The case is suitable for programs with a focus on marketing and competitive strategy. Students will learn issues in filmmaking and how the industry operates. They will also learn how to apply the 4 Ps framework (Pricing, Product, Place and Promotion) to marketing a new movie and how the Diffusion of Innovations theory can help speed up the movie adoption rate.